О некоторых литуанизмах в польских и белорусских говорах - Веренич, В'ячеслав Леонтійович (Baltistica, 1989)
SOME LITHUANISMS IN THE POLISH AND BYELORUSSIAN DIALECTSAs a result of the analysis of the wordstock of two Polish dialects in Trakai and Švenčionys districts of the Lithuanian SSR 78 words of the Lithuanian origin are singled out, 24 of which are not mentioned in the “Dictionary of Baltisms in the Slavic Languages” by J. Laučiutė (1982). A separate article is dedicated to each lexeme and possible Byelorussian parallelisms, a Lithuanian source being pointed out. The analysed vocabulary is conditionally divided into three groups : (1) words with obvious Lithuanian etymology and without Slavic analogs (ʒ’ˊašra, g’adˊory/g'ǝad'uk’i, grud'oły, kam’en̛'ulk’i, kam’en̛'ulka/boŋk, kr'ei̯ci, łał'own̛'ik’i, łał'ymk’i); (2) words with insufficient Lithuanian etymology and possible Slavic analogs (b'apk’i, c’ˊužka, kak'ory, p’ˊelcy, p’erʒ’ˊołk'i, r'uŋkli, s’m'igla, šm'yrg’el, tark'ovac’, traxn̛'ica, vanʒ’ˊuška);(3) words having analogs in the Slavic languages and considered Lithuanisms only according to some characteristics (bulb’ˊaŋka, k'ombel, kr'oŋkač kr'oŋka, płai̯sk'ońe, tęnšč).